Situation of the increasing pressure of genetic abnormalities in a diploid-polyploid of population spined loaches (Cypriniformes, Cobitidae, Cobitis) - Mezhzherin, S.V.; Tsyba, A.A.; Mezhzherina, D. S.; Pukhtaevitch, P.P. (Reports of the National Academy of Sciences of Ukraine, 2014)
Genetic monitoring of a diploid-polyploid population of spined loach (Cobitis taenia s. lato) in the Irpen river (tributary of the Dnieper) has pointed unusually abrupt changes of its biot C. 2 elongatoides-tanaitica biotype with abnormal allozyme spectrum became to completely dominate. At the same time, individuals of this population also demonstrate a sharp increase in the number of binuclear erythrocytes. All these negative genetic processes occurred against the background of a declining population of the species in this river, which indirectly indicates a slight decrease in the fitness of individuals of this population.